How enamel thickness, mineral concentration and mechanical properties influence tooth wear and fractures in catarrhine molar crowns - Towle, Ian; Hlusko, Leslea J.; De Pinillos, Marina Martinez; Modesto, Mario; Irish, Joel D.; Loch, Carolina (American Journal of Biological Anthropology, 2024)
[Resumen no disponible]
Keywords: mineral concetration; mechanical properties